A Comparative Analysis of Catholic Educational Concepts: the Case of Jesuit and Fr. Luigi Giussani’s Concepts - Labokas, Juozapas (Acta Paedagogica Vilnensia, 2019)
Currently, value-based education occupies a leading position within the contemporary academic discourse on education. Catholic education holds a decent share in this overall discussion. This is partly due to the growing number of Catholics in Africa and Asia as well as globalization and secularization processes. Considering this fact, the philosophical underpinnings of Catholic education, its identity issues, and future perspectives are gaining more and more attention from the academic audience worldwide. In this study, an attempt was made to examine and compare two different concepts of Catholic education, one of Italian Catholic priest Fr. Luigi Giussani and that of the Jesuits. The research was aimed at analyzing and evaluating the similarities and differences of these concepts, revealing their interrelation. The analysis showed that these educational concepts have only slightly different goals and use different wording to define their aims. This situation is preconditioned by different historical-cultural contexts and experiences. In conclusion, Jesuit education tends to stress academic achievements and a value-based education approach, while Giussani’s concept emphasizes an interest in showing the importance and meaning of human reality and value education through its verification according to real-life needs. This allows to categorize Jesuit education as more traditionally-Catholic oriented while viewing Giussani’s concept as more suitable for Western secularized societies, which are not or less familiar with such notions as fate, religion, Christianity, God, etc. Despite the fact that these concepts employ different educational methods and approaches and have only slightly different goals, their interrelationship can be described as complementary rather than differentiated or competing.